A co-simulation study of differential braking electronic stability control for vehicle lateral stability - Shrestha, Rohan; Silwal, Sanjog; Raut, Debendra Bahadur (Journal of Innovations in Engineering Education, 2026)
This paper focuses on the design and simulation of a non-linear electronic stability control (ESC) system using MATLAB/Simulink, and validated through co-simulation with CarSim multibody dynamics (MBD) software. The ESC controller was designed in MATLAB/Simulink using sliding mode control technique due to its robust behavior under non linearities, uncertainties, and disturbances. The controller utilized differential braking in order to generate corrective yaw moment that improves the lateral stability of the vehicle. For simulation, a front wheel driven C-class hatchback was used. The controller was evaluated using the sine with dwell (SwD) and tight double lane change (TDLC) tests within CarSim. The SwD was evaluated using the FMVSS 126 ESC homologation standards and the results demonstrated a reduction in the yaw rate NRMSE from 1.094 to 0.118 and sideslip angle NRMSE from 5.811 to 0.271. The DLC test was performed at 120 kmph which also demonstrated significant improvement in lateral path tracking.